(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe the current status of knowledge and attitudes toward ostomy self-care and to identify factors associated with knowledge and attitudes among patients with ostomies at Hanoi Medical University Hospital in 2025. Subjects and methods: A cross-sectional descriptive study was conducted among 74 patients with ostomies who were receiving inpatient treatment or follow-up care at the Colorectal and Pelvic Floor Surgery Department, Hanoi Medical University Hospital from January to April 2025. Patients’ ostomy self-care knowledge was assessed using a 29-item multiple-choice questionnaire. Attitudes toward ostomy self-care were measured using a 6-item questionnaire. Data were processed and analyzed using SPSS version 26.0, applying descriptive statistics and Chi-square tests to examine associations between variables. Results: The majority of patients were male (63.5%). The mean age was 61.22 ± 14.23 years. Overall, 75.7% of patients demonstrated adequate ostomy self-care knowledge. The highest knowledge scores were observed in the nutrition domain (81%), whereas other domains, including ostomy care techniques, management of complications, and lifestyle-related practices, remained limited. Regarding attitudes, only 13.5% of patients exhibited a positive attitude toward ostomy self-care; 60.8% had a neutral attitude, and 25.7% had a negative attitude. Knowledge was significantly associated with age, educational level, occupation, sources of information, and duration of living with an ostomy (p < 0.05). In addition, a statistically significant association was found between knowledge and attitudes toward ostomy self-care (p = 0.036). Conclusion: Patients’ knowledge and attitudes toward ostomy self-care remain limited. Strengthening health education and communication activities, providing individualized counseling, and offering psychological support are necessary to improve self-care effectiveness and enhance the quality of life of patients with ostomies.